POLITIK HUKUM DALAM KEBIJAKAN PENGAWASAN ARTIFICIAL INTELLIGENCE DI SEKTOR PUBLIK INDONESIA - Opik Sepriadi; Mustofa Kamil; Salman Al Ghifari; Unggul Budi; Ridwan; Oke Wiredarme (CV. Lafadz Jaya, 2026)
Advances in Artificial Intelligence (AI) technology have brought about significant transformations in modern governance, including in Indonesia. The use of AI in the public sector raises a range of complex legal challenges, ranging from the protection of personal data and algorithmic accountability to the transparency of automated decision-making. This paper analyses the legal policy regarding AI oversight in Indonesia’s public sector using an approach grounded in constitutional law and technology law. The research employs a normative legal research method with a conceptual and comparative legal approach. The findings indicate that the legal policy on AI oversight in Indonesia remains fragmented and reactive, dominated by a sectoral approach rather than a holistic one. This study recommends the need for a specific law on AI that integrates principles of algorithmic ethics, the protection of fundamental rights, and independent oversight mechanisms to ensure accountability in the use of AI within governance.